GADD45B Promotes Glucose-Induced Renal Tubular Epithelial-Mesenchymal Transition and Apoptosis via the p38 MAPK and JNK Signaling Pathways - Xue, Mei; Sun, Hongxi; Xu, Rong; Wang, Yue; Guo, Jun; Li, Xiaoyu; Cheng, Ying; Xu, Chaofei; Tang, Chao; Sun, Bei; Chen, Liming (Frontiers in Physiology, 2020)
Growth arrest and DNA damage-inducible beta (GADD45B) is closely linked with cell cycle arrest, DNA repair, cell survival or apoptosis in response to stress and is known to regulate the mitogen-activated protein kinase (MAPK) pathway. Here, using an RNA sequencing approach, we determined that GADD45B was significantly upregulated in diabetic kidneys, which was accompanied by renal tubular epithelial-mesenchymal transition and apoptosis, as well as elevated MAPK pathway activation. In vitro, GADD45B expression in cultured HK-2 cells was also stimulated by high glucose. In addition, overexpression of GADD45B in HK-2 cells exacerbated renal tubular epithelial-mesenchymal transition and apoptosis and increased p38 MAPK and JNK activation, whereas knockdown of GADD45B reversed these changes. Notably, the activity of ERK was not affected by GADD45B expression. Furthermore, inhibitors of p38 MAPK (SB203580) and JNK (SP600125) alleviated high glucose- and GADD45B overexpression-induced renal tubular epithelial-mesenchymal transition and apoptosis. These findings indicate a role of GADD45B in diabetes-induced renal tubular epithelial-mesenchymal transition and apoptosis via the p38 MAPK and JNK pathways, which may be an important mechanism of diabetic kidney injury.